Early Edema Within the Ischemic Core Is Time-Dependent and Associated With Functional Outcomes of Acute Ischemic Stroke Patients - Han, Qing; Yang, Jianhong; Gao, Xiang; Li, Jichuan; Wu, Yuefei; Xu, Yao; Shang, Qing; Parsons, Mark W.; Lin, Longting (Frontiers in Neurology, 2022)
Objective To investigate the difference in early edema, quantified by net water uptake (NWU) based on computed tomography (CT) between ischemic core and penumbra and to explore predictors of NWU and test its predictive power for clinical outcome. Methods Retrospective analysis was conducted on patients admitted to Ningbo First Hospital with anterior circulation stroke and multi-modal CT. In 154 included patients, NWU of the ischemic core and penumbra were calculated and compared by Mann–Whitney U test. Correlations between NWU and variables including age, infarct time (time from symptom onset to imaging), volume of ischemic core, collateral status, and National Institutes of Health Stroke Scale (NIHSS) scores were investigated by Spearman's correlation analyses. Clinical outcome was defined using the modified Rankin Scale (mRS) at 90 days. Logistic regression and receiver operating characteristic analyses were performed to test the predictive value of NWU. Summary statistics are presented as median (interquartile range), mean (standard deviation) or estimates (95% confidence interval). Results The NWU within the ischemic core [6.1% (2.9–9.2%)] was significantly higher than that of the penumbra [1.8% (−0.8–4.0%)]. The only significant predictor of NWU within the ischemic core was infarct time (p = 0.004). The NWU within the ischemic core [odds ratio = 1.23 (1.10–1.39)], the volume of ischemic core [1.04, (1.02–1.06)], age [1.09 (1.01–1.17)], and admission NHISS score [1.05 (1.01–1.09)] were associated with the outcome of patients adjusted for sex and treatment. The predictive power for the outcome of the model was significantly higher when NWU was included (area under the curve 0.875 vs. 0.813, p < 0.05 by Delong test). Conclusions Early edema quantified by NWU is relatively limited in the ischemic core and develops in a time-dependent manner. NWU estimates within the ischemic core may help to predict clinical outcomes of patients with acute ischemic stroke.